STRATEGY FOR DEVELOPMENT OF ORGANIC FERTILIZER BUSINESS IN EFFORTS TO INCREASE COMPETITIVENESS AND SUSTAINABLE AGRICULTURE - I Made Budiasa; Ni Putu Anglila Amaral (International Journal of Applied Science and Sustainable Development (IJASSD), 2022)
Sustainable agriculture is the use of renewable and non-renewable resources for the agricultural production process by minimizing the negative impact on the environment to a minimum. Economically profitable and accountable. Farmers are able to generate profits in sufficient and stable production levels, at an acceptable level of risk. With an ecological perspective, the quality of agroecosystems is maintained or improved, by maintaining ecological balance and conserving biodiversity. Organic farming is one of the implementations of sustainable agriculture. The shift in the use of chemical inputs to organic inputs has an optimal effect on potential environmental conservation. Therefore, organic fertilizer is very potential to be developed in the agricultural business. The results showed that the internal factor is the quality of human resources in adopting integrated agriculture through the use of organic fertilizers and product quality is highly dependent on climatic factors. External factors are seen in the development of globalization with digital marketing and competition for fertilizer products on a global scale. The alternative strategy is the Strenght Opportunity Strategy, namely improving the quality of organic fertilizers, optimizing organizational management and prioritizing customer satisfaction.